Payment for Watershed Services: A Potential Tool for Sustainable Tourism in Indian Himalayas - Badola, Srishti; Rana, Sakshi (Indian Forester, 2016)
Tourism in India has emerged as one of the biggest contributors to the nation's gross national product (GDP) and predictions say that it will only keep growing. With technological advancement, an increase in awareness among the masses and increased spending power, the number of tourists is increasing. This has put a massive burden on the natural resources like water, air and forest ecosystem of tourist spots leading to their scarcity. Water scarcity already is looming over many regions in India, including one of the major tourist hotspots and water tower- the Indian Himalayas. The problem is increasing with unprecedented population growth, unplanned development and climate change. Another major concern is declining forest cover, which provides important watershed services like quantity and flow. In this paper, we have tried to link payment for watershed services (PWS) with tourism sector in the Indian Himalayas, a potential tool to link local livelihoods with healthy and functional ecosystems.